Money and Its Role of Income Stabilization: An Econometric Diagnosis - Paudel, Bamadev (NRB Economic Review, 2003)
There is a continuous debate over the transmission mechanism of monetary impulses on economic activities in developed as well as developing countries, and the debate revolves around two broad categories of transmission channels- the Keynesian and the Quantity Theory. Keynesian transmission mechanism examines the effect of money on economic activities by building the structural model. The basic Keynesian view is that the impact of the change in money stock on real income results indirectly through change in the rate of interest rate and thereby investment expenditure. The Quantity Theory of Money, on the other hand, is associated with reduced-form economic model, in which the effect of money on economic activities is examined by looking whether movements in income are tightly linked to movements in money supply. Monetarists analyze the effect of change in money supply on the change in income level as if the economy is a black box in which its working can not be detected. This paper tries to find out the relationship between money and income by using reduced-form models. The empirical results show that there is a strong positive association between money and its role of income stabilization. It is true both for nominal as well as real terms. The lagged response of money supply on income is two years in nominal terms and three years in real terms. There is also the structural shift in the role of money for income stabilization, indicating that money has become more effective during the liberalization period to determine the income level of the economy.